Stand spatial structure promotes tree growth and sapling diversity in northern tropical karst seasonal rainforest - Li, Lingyan; Ma, Ruixia; Wang, Bin; Huang, Fuzhao; Li, Jianxing; Lu, Fang; Xiang, Wusheng; Li, Dongxing; Li, Xiankun; Guo, Yili (Frontiers in Plant Science, 2025)
Stand spatial structure and sapling diversity are essential for maintaining ecosystem stability. However, the dynamic characteristics of stand spatial structure, its driving factors, and its influence on sapling diversity remain unclear. This study was conducted in a 15-ha forest dynamics plot located in the seasonal rainforest of the northern tropical karst region. We analyzed stand dynamics by characterizing multivariate distributions of stand spatial structure within random structural units, together with stand growth, mortality, and recruitment processes. To evaluate spatial autocorrelation and its drivers, we constructed spatial lag models and spatial error models. Generalized additive models were further applied to assess the effects of topography on stand spatial structure, as well as the influence of stand spatial structure on sapling diversity. The overall stand exhibited a uniform angle index of 0.5, a mingling index of 0.75, and a dominance index of 0.49, indicating random species distribution with moderate to high mingling. Null, univariate, bivariate, and trivariate distributions of stand spatial structure exhibited no significant change over the past decade. At the individual-tree level, however, survival, mortality, and recruitment processes induced notable shifts in spatial structure, which were more pronounced than the overall stand-level dynamics. Topography strongly influenced spatial structural metrics: elevation explained 31.35% and 64.99% of the variance in mingling and dominance, respectively, making it the most important factor for these indices, while slope accounted for 22.53% of the variance in the uniform angle index, serving as its primary driver. Among structural attributes, mingling had overwhelming explanatory power for sapling diversity, accounting for 99.68% of the variance in the Shannon–Wiener index, 99.70% in the Simpson index, 54.88% in Pielou’s evenness index, and 99.69% in Margalef’s diversity index, identifying it as the dominant factor regulating sapling diversity. These findings demonstrate that considering the dynamic changes of stand spatial structure at the individual-tree level, together with its effects on sapling diversity, is essential for understanding the structural and functional properties of tropical karst forests.